AN EXPLORATION OF LEARNERS’ FOREIGN LANGUAGE ANXIETY IN THE INDONESIAN UNIVERSITY CONTEXT: LEARNERS’ AND TEACHERS’ VOICES - Subekti, Adaninggar Septi (TEFLIN Journal, 2018)
Despite the importance of teachers’ roles in helping learners overcome their foreign language anxiety (FLA), a number of studies found that there were some mismatches between learners’ views and those of the teachers in regard with learners’ FLA. These mismatches could potentially hinder the teaching and learning process. This study, therefore, investigated the views of Indonesian university students from non-English majors and their teachers on the effects of and factors associated with FLA. It involved six English 3 (General English class) students from different anxiety levels, low-anxiety, medium-anxiety, and high-anxiety, and six teachers of English 3. Through Thematic Analysis, the study found six emerging themes regarding the teachers’ and students’ views on the effects of FLA and factors associated with FLA. The first theme was on their views on the effects of FLA. The other five themes were on contributing factors of FLA, teachers’ attributes, teachers’ perceived efforts, students’ attributes, and interactions as well as activities in class. Based on the results and the limitations of the study, implications and recommendations for students, teachers, and future researchers were also presented.